2008
DOI: 10.1016/j.ejheart.2008.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional electrical stimulation on quality of life and emotional stress in patients with chronic heart failure secondary to ischaemic or idiopathic dilated cardiomyopathy: A randomised, placebo‐controlled trial

Abstract: Objective: Functional electrical stimulation (FES) improves exercise capacity and endothelial function in chronic heart failure (CHF) patients. This study evaluates the impact of FES on quality of life and emotional stress in patients with moderate to severe CHF. Methods: Thirty patients with stable CHF (24 men; NYHA class II-III; left ventricular ejection fraction b35%) were randomly assigned (2:1) to a 6-week FES training program (n = 20) or placebo (n = 10). Questionnaires addressing quality of life [Kansas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 20 publications
0
41
0
2
Order By: Relevance
“…Recently, improvement in QOL has been reported in high-intensity interval training 40,73-75 and electrical muscle stimulation therapy in patients with severe heart failure. 76 Further studies are required to establish evidence.…”
Section: Methodology Of Cardiac Rehabilitation To Improve Qolmentioning
confidence: 99%
“…Recently, improvement in QOL has been reported in high-intensity interval training 40,73-75 and electrical muscle stimulation therapy in patients with severe heart failure. 76 Further studies are required to establish evidence.…”
Section: Methodology Of Cardiac Rehabilitation To Improve Qolmentioning
confidence: 99%
“…34) Accumulating evidence suggests that CR, such as exercise training for patients with CHF, can improve HR-QOL. 20,35) Thus, early detection and appropriate intervention into depression would be greatly needed in addition to treatment for background CVDs. 36,37) Relative to other CVD, such as CAD and CHF, the impact of HT on HR-QOL may be less, but it is reported that psychosocial factors contribute to the development of HT, and a higher level of BP induced more physical, emotional, and psychosocial impairments.…”
Section: Discussionmentioning
confidence: 99%
“…The research demonstrated that the application of NMES in patients with CHF results in improvement of exercise tolerance indicators, such as: increased peak oxygen consumption, increased anaerobic threshold, increased duration of exercise tests and greater distance covered during the 6MWT test [9][10][11][12][13][14][15][16][17][18][19][20]. After a series of NMES treatment sessions, increased muscle endurance was also noted in patients with CHF [12].…”
Section: Application Of Nmes In Patients With Chronic Heart Failurementioning
confidence: 99%
“…In patients with CHF, the duration of muscle contraction was short and amounted to approx. 2 seconds [13,21,22] or 5-6 seconds [9,12,17] with contractions lasting about 10 seconds [11] or even 20 seconds [14,15] being used less often. The relaxation period lasted as long as the contraction or 2-3 times longer at most [13,21,22].…”
Section: Application Of Nmes In Patients With Chronic Heart Failurementioning
confidence: 99%
See 1 more Smart Citation